Increasing the Effectiveness of Facebook Ads Campaign: A Case Study on Video Advertising - Mohamad Rizal, Nur Irdina Aniqah; Zuhairi, Nurin Ellisya; Mohd Nasri, Nur Putri Balqis; Md Maarof, Mohd Zulariffin (Multidisciplinary Applied Research and Innovation, 2025)
Ads campaigns, aiming to enhance engagement and conversion rates. Leveraging Facebook’s vast user base, businesses increasingly utilize dynamic video content for targeted advertising. The study analyzes key factors such as content quality, video length, audience targeting, and call-to-action (CTA) effectiveness. Data from various campaigns indicate that high-quality, concise videos with clear messaging and strong CTAs perform significantly better. Effective audience segmentation based on demographics and interests also boosts engagement and conversions.